Analisis Unsur Intrinsik Dalam Komik Solo Leveling Karya Chu-Gong - Levi Al Kausar (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This article provides an in-depth analysis of the comic "Solo Leveling" by Chu-Gong, focusing on the storyline, characters, setting, themes and messages conveyed. The storyline begins with the introduction of a modern fantasy world inhabited by Hunters, warriors with magical powers, who fight against monsters from the dungeon. Sung Jin Woo, as the weakest Hunter, becomes the central point of the story after being selected by a mysterious system that gives him rare abilities. Sung Jin Woo's battles against various enemies, including humans and monsters, become the center of the story, while character analysis reveals Sung Jin Woo's emotional complexity and key role in the narrative. The story's detailed settings, diverse dungeon locations, and diverse cultures and races provide a strong visual framework for readers. Themes such as power, battle, and dungeon secrets dominate the story, giving depth to the narrative. The messages that emerge involve struggle and survival, mystery, increasing power, conflict against humans and monsters, and the discovery of secrets and sources of power. With the combination of these elements, "Solo Leveling" offers an immersive reading experience, motivating readers to continue following Sung Jin Woo's epic journey and exploring a world full of mystery, magic and exciting battles.